2008
DOI: 10.1177/1356766707084218
|View full text |Cite
|
Sign up to set email alerts
|

Measuring tourist satisfaction by attribute and motivation: The case of a nature-based resort

Abstract: Measuring tourist satisfaction plays an important role in marketing tourism products and services. The purpose of this study is to examine the relationship between destination attribute importance and performance, travel motivation, and satisfaction. It is hypothesized that tourist satisfaction of a destination is a function of attribute importance, performance, and travel motivation. A nature-based resort, serving as a short-term family vacation destination in South-east Virginia, was used as the study site f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
61
0
5

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 308 publications
(70 citation statements)
references
References 40 publications
4
61
0
5
Order By: Relevance
“…The importance of the dimensions of quality on the basis of this model confirms the previous results (Table 7); the order of the dimensions is almost identical to the previous model. The obtained results correspond with the research by Meng et al (2008) which revealed that destination quality does not only concern outdoor activities and natural scenery but it is also dependent on the provision of elements such as friendly service and quality lodging facilities. The regression models mentioned above were evaluated by means of F-test as statistically significant.…”
Section: /849supporting
confidence: 74%
“…The importance of the dimensions of quality on the basis of this model confirms the previous results (Table 7); the order of the dimensions is almost identical to the previous model. The obtained results correspond with the research by Meng et al (2008) which revealed that destination quality does not only concern outdoor activities and natural scenery but it is also dependent on the provision of elements such as friendly service and quality lodging facilities. The regression models mentioned above were evaluated by means of F-test as statistically significant.…”
Section: /849supporting
confidence: 74%
“…IsoAhola (1989) argued that tourism motivations, including escaping purpose and hunger for learning, are essential for subjective well-being (Iso-Ahola, 1980;Kim, Woo, & Uysal, 2015). Previous studies have shown that the most common nature-based tourist motivations include novelty, rest and relaxation, social/family relationship, and self-fulfillment (Kastenholz & Rodrigues, 2007;Lang & O'leary, 1997;Meng et al, 2008). These motivations are a part of a higher order of needs in Maslow's hierarchical needs dimension (Clarke, Islamm, & Paech, 2006;Maslow, 1954).…”
Section: Motivation and Personal Values And Their Relation To Subjecmentioning
confidence: 97%
“…Schofield and Thompson (2007) established that satisfaction and behavioral intentions are significant outcomes of attending festivals. Although tourism research has been utilizing mainly satisfaction and behavioral intentions as outcome constructs (Devesa, Laguna, & Palacios, 2010;Meng, Tepanon, & Uysal, 2008), it has been shown that subjective well-being is also an important outcome of tourist motivation. IsoAhola (1989) argued that tourism motivations, including escaping purpose and hunger for learning, are essential for subjective well-being (Iso-Ahola, 1980;Kim, Woo, & Uysal, 2015).…”
Section: Motivation and Personal Values And Their Relation To Subjecmentioning
confidence: 99%
“…These studies have made a significant contribution to the tourism sector, especially in the development of marketing strategies and positioning for destinations [11]. They also have provided useful knowledge to the tourism, travel, transport and hospitality sectors in general, contributing to their sustainability in an increasingly competitive environment [12,13,58,59].…”
Section: Satisfaction Image and Nautical Tourist Behaviourmentioning
confidence: 99%